Un inedito testo di Chimica Applicata di Francesco Mauro - Colella, Carmine; D’Auria, Maurizio (Chimica nella Scuola, 2022)
A rare and unknown text on Applied Chemistry written by Francesco Mauro, a pupil of Stanislao Cannizzaro, who was full professor of Docimastic Chemistry at the Naples School of Engineering at the end of the nineteenth century, is examined and commented on. Mauro is recognized as one of the most active Italian teachers in the transition from Docimastic Chemistry to Applied Chemistry, i. e. from the chemistry of “essays” to the chemistry of materials, an intermediate step towards the Science and Technology of Materials, which is currently being taught to industrial Engineering students. This paper also makes it possible to highlight Mauro’s great teaching skills and the care taken in the acquisition of original data produced by the leading Applied Chemistry scientists of the second half of the nineteenth century.